THE ROLE OF PASSER (PAGUYUBAN AJEN SUNDA SEJA RAHARJA) ORGANIZATION IN BUILDING OF RESPOSIBILITY CHARACTER SOCIETY - Susan Fitriasari, Yusup Bachtiar Rahmat (Department of Civic Education, 2016)
This research is motivated by appearance of some community organization which is not equal between quantity and quality as an organization of community empowerment. Existing community organization disoriented as thuggery and not maximal in community servicing. Community organization which conducted by the author in Sekepicung Village, Ciburial, shows that there is one community organization called PASSER (Paguyuban Ajen Sunda Seja Raharja). This research use qualitative research method with study case of some research subjects including PASSER members and caretakers, Sekepicung village community, and the head of RW 05 Sekepicung village. Data collecting is through observation, interview, literacy study, documentation, and note field. The result of this research shows that: 1) Programmes of PASSER to develop community cares is assessment programme or data estimation of community situation and programmes which contain mutual corporation and social service; 2) PASSER use emotional approach strategy and also interest and talent approach in the principle of family and kinship; 3) Barriers of PASSER including internal factor which is human resources and external factor which is conflict between PASSER and neighbourhood association caretaker. 4) The effort of PASSER to resolve that barrier is quality improvement of human resource specially in administration ability, develop good relationship with others organization, and build good communication with the neighbourhood association care taker.Keyword: Responsibility Character, Community Organization, Sekepicung Village, Character Building